3
$\begingroup$

I was struggling to factorize this expression, I need it cleaned to bracket form but I was struggling to understand the process to get the answer? Is there a special formula or technique for factorizing these sorts of expressions?

$$1 - y-x^2-y^2-yx^2+y^3$$

Answer: $$ \ ( 1+y)[(1-y)^2-x^2] $$

$\endgroup$
2
  • $\begingroup$ There is no easy or obvious way to factor multivariate polynomials. $\endgroup$ Jan 2 '20 at 18:03
  • $\begingroup$ Yeah, you just need to play around with the expression and hopefully recognize a pattern that resembles something you've seen before. $\endgroup$ Jan 2 '20 at 18:45
7
$\begingroup$

Factoring multivariable polynomials usually needs a bit of creativity. However, when looking for an approach, you can always think of multivariable polynomials as polynomials over a single variable whose coefficients are another polynomials!

With a bit of creativity: $$\begin{align} 1 - y-x^2-y^2-yx^2+y^3 &= \underbrace{(1-y-y^2 +y ^3)}_{\text{only y dependent}}-\overbrace{(x^2 +yx^2)}^\text{also x dependent}\\ \\ &= (1-y-y^2 +y ^3)-x^2(1+y). \\\\ \end{align}$$

If we plug $y = -1$, we have $(1+1-1-1)+x^2(1-1) \equiv 0.$ So we can divide this expression by $(1+y)$, and obtain the desired result or factorize even further to get

$$\begin{align}(1+y)( (y^2-2y+1) - x^2) &= (1+y)((y-1)^2-x^2)\\\\ &= \boxed{(1+y)(y-1-x)(y-1+x).}\end{align}$$

A more deep argument of why I tried this method: note that this expression is cubic over $y$. So if you can factorize this polynomial $p(x,y)$ into $q(x,y)r(x,y)$, either $q$ has degree $1$ over $y$ or $q$ has degree $2 \implies r$ has degree $1$. So there's a rational function $g(x)$ such that $p(x,g(x)) = 0$. So we need a factor of the form $k(x)y - l(x)$.

Note that you could use this last argument to deduce the same thing for $x$. So getting $x^2 = k(y)/l(y)$ is also a good guess.

$\endgroup$
1
  • 2
    $\begingroup$ Why did this get downvoted? $\endgroup$ Jan 2 '20 at 17:21
2
$\begingroup$

Note $x^2$ is the only $x$-term,

$$1 - y-x^2-y^2-yx^2+y^3$$ $$=1-y-y^2+y^3 -(1+y)x^2$$ $$=(1-y) -y^2(1-y) -(1+y)x^2$$ $$=(1-y)(1-y^2)-(1+y)x^2 =(1+y)(1-y)^2-(1+y)x^2 $$ $$= ( 1+y)[(1-y)^2-x^2] $$

$\endgroup$
2
$\begingroup$

Once you gave us the answer, the factoring became easy. You just have to look for the factor $1+y$

$$1 - y-x^2-y^2-yx^2+y^3= (1+y^3)-(y+y^2)-x^2(1+y)$$

$$=(1+y)(1-y+y^2)-y(1+y)-x^2(1+y)=(1+y)(1-y+y^2-y-x^2)$$

$$=(1+y)[(1-y)^2-x^2]$$

$\endgroup$
1
$\begingroup$

Here is how I factored it:

$$1-y-x^2-y^2-yx^2+y^3=$$ $$(1-y^2)-(y-y^3)-(x^2+yx^2)=$$ $$(1-y^2)-y(1-y^2)-x^2(1+y)=$$ $$(1-y^2)(1-y)-x^2(1+y)=$$ $$(1-y)(1+y)(1-y)-x^2(1+y)=$$ $$(1+y)(1-y)^2-(1+y)x^2=$$ $$\boxed{(1+y)[(1-y)^2-x^2]}$$

You can factorize it further:

$$(1+y)[(1-y)^2-x^2]=$$ $$(1+y)[(1-y-x)(1-y+x)]=$$ $$\boxed{(1+y)(1-y-x)(1-y+x)}$$

We can expand $(1+y)(1-y-x)(1-y+x)$ to make sure we got it:

$$\require{cancel} (1+y)(1-y-x)(1-y+x)=$$ $$(1\cancel{-y}-x\cancel{+y}-y^2-xy)(1-y+x)=$$ $$(1-x-y^2-xy)(1-y+x)=$$ $$(1-x-y^2-xy)-(y-xy-y^3-xy^2)+(x-x^2-xy^2-x^2y)=$$ $$1\cancel{-x}-y^2\cancel{-xy}-y\cancel{+xy}+y^3\cancel{+xy^2}\cancel{+x}-x^2-\cancel{xy^2}-x^2y=$$ $$1-y^2-y+y^3-x^2-x^2y=$$ $$\boxed{1-y-x^2-y^2-yx^2+y^3}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.